Perancangan Interior Kabinet Coffee di Surabaya - Christine Amelia Gunawan (Intra, 2016)
Kabinet Coffee is the only one coffee shop in Surabaya, which provides information about the coffee to visitors, not only for commercials purposes but it can show some information about the coffee. The purpose of interior design of Kabinet Coffee in Surabaya is to provide coffee center that sells coffee drinks and food as well as providing Indonesian coffee information by opening a new of an existing Kabinet Coffee. The facilities rooms are café, shop, gallery, workshop room, and multifunction room. Kabinet Coffee design is inspired by the specialist coffee of Kabinet Coffee, Papua Wamena coffee. The concept is taken by themed Papua combined with elements of coffee. The concept is applied to the interior elements to take Asmat elements like shield, mask, sculpture, house, and boat, also take red and brown colors. And the concept take from coffee elements like round shape and brown color.